Low PDCD4 Expression Is Associated With Poor Prognosis of Colorectal Carcinoma. Issue 9 (October 2021) - Kim, Joo Young; Lee, Hojung; Kim, Eun Kyung; Lee, Won Mi; Hong, Young Ok; Hong, Soon Auck
Abstract : Programmed cell death 4 (PDCD4) is a tumor suppressor gene that inhibits tumor progression, invasion, and metastasis. Decreased PDCD4 expression is associated with poor prognosis in various types of cancers. We evaluated PDCD4 expression and its clinicopathologic correlation, including patient survival, in 289 surgically resected colorectal cancers. Low nuclear PDCD4 expression was identified in 177 (61.2%) cases and was associated with large tumor size, high pT classification, and the presence of lymphovascular and perineural invasion. The 5-year survival rate of patients with low nuclear PDCD4 expression was significantly lower than that of patients with high expression (72.2% vs. 93.3%, P <0.001). American Joint Committee on Cancer stage II and III colorectal cancer patients with low nuclear PDCD4 expression (76.9% and 67.2%, respectively) showed significantly worse overall survival than those with high expression (100% and 92.9%, P =0.002 and 0.032, respectively). Low nuclear PDCD4 expression was an independent poor prognostic factor in colorectal cancer patients (hazard ratio=3.556; 95% confidence interval, 1.739-7.271; P =0.001). Our study suggests that low PDCD4 expression is associated with aggressive behavior and can be used as a prognostic indicator of colorectal cancer patients.